Eksistensi Masyarakat dan Pengaruh Agama - Adi Saingo, Yakobus (LP2M UIN Sunan Kalijaga, 2024)
The relationship between society and religion has experienced ups and downs, because there are members of the community who see religion as the foundation of moral and spiritual values, but there are also many people who perceive religion as a mistake that mankind believes in. But even so, the existence of society cannot be separated from religion and its influence. The existence of society is quite identical as religious beings. The purpose of this study is to find out and explain the existence of society and the influence of religion, including the existence of individuals as part of society which is quite influenced by religion, and the functions of religion, as well as the dynamics of religious theory which is quite influencing the existence of society. The research method used is literature research by collecting data from various literature such as journals published in the last 5 years. The results of the study and analysis of the data found that there were developing dynamics of religious theory that sufficiently influenced the existence of society, including: the theory of evolution, the theory of marxism, the theory of thermodynamics and the theory of liberalism. Religion also has an impact through its function for the existence of society, including: as a source of value in maintaining decency, a means of solving problems, a means of satisfying curiosity. Apart from that, in the context of the influence of religion in society, several forms of influence have been identified, namely: educative influence, giving awareness about safety, its effect as conciliation, its influence as social control, its influence in strengthening solidarity, its influence in transformative values, religious encouragement to be productive, motivation sublimative. [Hubungan masyarakat dengan agama mengalami pasang-surut, karena ada anggota masyarakat yang melihat agama sebagai pondasi nilai moral dan spiritual, namun banyak juga kalangan masyarakat yang menganggap agama sebagai suatu kesalahan yang dipercayai umat manusia. Namun sekalipun demikian, eksistensi masyarakat tidak dapat dipisahkan dari agama dan pengaruhnya. Eksistensi masyarakat cukup identik sebagai makhluk beragama. Tujuan penelitian ini untuk mengetahui dan menjelaskan mengenai eksistensi masyarakat dan pengaruh agama, di antaranya eksistensi individu sebagai bagian dari masyarakat yang cukup dipengaruhi agama, dan fungsinya agama, serta dinamika teori keagamaan yang cukup mempengaruhi keberadaan masyarakat. Metode penelitian yang digunakan yaitu literature research dengan mengumpulkan data dari berbagai literatur seperti buku jurnal yang diterbitkan 5 tahun terakhir. Hasil kajian dan analisis data ditemukan bahwa terdapat dinamika teori keagamaan yang berkembang sehingga cukup mempengaruhi eksistensi masyarakat, antara lain: Teori evolusi, teori marxisme, teori thermodynamics dan teori liberalisme. Agama juga berdampak melalui fungsinya bagi eksistensi masyarakat, di antaranya: sebagai sumber nilai dalam menjaga kesusilaan, sarana mengatasi permasalahan, sarana memuaskan perasaan ingin tahu. Selain itu pada konteks pengaruh agama dalam Masyarakat maka telah diketahui beberapa bentuk pengaruh, yaitu: pengaruh edukatif, memberi kesadaran tentang keselamatan, pengaruhnya sebagai pendamaian, pengaruhnya sebagai kontrol sosial, pengaruh dalam memperkuat solidaritas, pengaruhnya dalam nilai transformatif, dorongan agama untuk produktif, motivasi yang sublimatif.]